MODERN TRENDS AND INNOVATIONS IN TEACHING ECONOMIC TERMINOLOGY USING INFORMATION TECHNOLOGY - Inagamova Nargis Abdullayevna (Western European Studies, 2025)
This article explores the modern trends and innovations in teaching economic terminology through the use of information technology (IT). As the field of economics involves complex and specialized terms, integrating IT into the learning process provides an engaging and effective approach to vocabulary acquisition. The article examines various digital tools and platforms, such as online glossaries, interactive learning platforms, mobile applications, gamification, and augmented reality (AR)/virtual reality (VR) simulations, that enhance the comprehension of economic concepts. By integrating expert opinions and practical examples, the article illustrates how these technologies create dynamic learning environments that cater to individual student needs, improve long-term retention, and bridge the gap between theory and real-world application. Despite the promising advantages, the article also discusses challenges, such as the digital divide and the need for balanced teaching methods. The study concludes that the strategic use of IT in teaching economic terminology can significantly enhance students' linguistic competence and prepare them for the globalized economic landscape.
Keywords: Terminology; Information Technology; Interactive Learning